Fossil fruits of Canarium (Burseraceae) from Eastern Asia and their implications for phytogeographical history. (9th August 2018) - Han, Meng; Manchester, Steven R.; Wu, Yan; Jin, Jianhua; Quan, Cheng
Abstract : The genus Canarium contains approximately 78 species distributed in the Old World tropics and subtropics. Canarium is characterized by a distinctive drupaceous fruit with a trilocular endocarp derived from three fused pyrenes. Here, we describe new Canarium fossil fruits from the late Oligocene of the Yongning Formation, the Miocene of the Erzitang Formation, and the late Miocene of the Foluo Formation in Guangxi Province, South China, providing the first confirmed fossil occurrences of Canarium in eastern Asia. The fruits of Canarium guangxiensis Han & Manchester sp. nov. are ovoidal to spindle shaped, 22.8–34.3 mm long, and 10.7–14.6 mm wide. Computed tomography (CT) scan was used to study the morphological and anatomical characters of fossil and modern Canarium, facilitating identification of the fossil fruits. This new occurrence supplements other megafossil records of Canarium fruits from the Eocene in North America, the Eocene to Oligocene in Europe, the Oligocene in Africa, the Oligocene to Miocene in Asia and from the Pleistocene in Australia and the Pacific islands. The fossil record indicates a wide dispersal of Canarium over the Northern Hemisphere during the Eocene and Oligocene, followed by a geographical contraction during the Miocene as the result of its extinction from North America and Europe. The origin and migratory routes of this genus are not clearly resolved, but based on the fossils known so far, we hypothesize that Canarium may have had a North American Eocene origin, with subsequent spread to Eurasia and Africa, followed by dispersal to the Southern Hemisphere.